THE ACCOUNTING EXCHANGE. - Cowin, R. B.; Hartmann, A. A.; Heath, Leslie A. (The Accounting Review, 1942)
Abstract This article points out the deficiencies in early cost accounting methods. Early text books on cost accounting commonly carried a graphic presentation of what was known as the cost formula . The formula stated that material cost plus labor cost equals prime cost and prime cost plus manufacturing expense equals cost to make. These propositions and the figure representing them have almost vanished from recent accounting literature, but occasionally they do reappear. It is because of such reappearances that this critique is presented. The earliest attacks on the formula were made by accountants with a economic turn of mind who insisted that few manufacturers were so fortunate as to be able to establish the selling price of their products by adding the desired profit to theft peculiar costs to make and sell. It is certainly true that direct material is no less an asset because it is taken from stores and placed in process or because it is taken from process and placed in finished stock, at least if production is for an existing demand. Without attempting to decide what might or might not be wise business policy relative to producing goods for a market which fails to provide a selling price high enough to cover all costs, it might be noted that the implication of cost priorities does not enjoy universal acceptance.